Association between preoperative neurocognitive status and IDH1 mutation status in high-grade gliomas. Issue 2 (30th September 2022) - Liouta, Evangelia; Kalyvas, Aristotelis V; Komaitis, Spyridon; Drosos, Evangelos; Koutsarnakis, Christos; García-Gómez, Juan M; Juan-Albarracín, Javier; Katsaros, Vasileios; Kalamatianos, Theodosis; Argyrakos, Theodoros; Stranjalis, George
Abstract: Background: High-grade glioma (HGG) patients present with variable impairment in neurocognitive function (NCF). Based on that, isocitrate dehydrogenase 1 (IDH1) wild-type HGGs are more aggressive than IDH1 mutant-type ones, we hypothesized that patients with IDH1 wild-type HGG would exhibit more severe NCF deficits than their IDH1 mutant counterparts. Methods: NCF was assessed by Mini Mental Status Exam (MMSE), Trail Making Test (TMT), Digit Span (DS), and Controlled Word Association Test (COWAT) tests in 147 HGG patients preoperatively. Results: Analyses between IDH1 groups revealed a significant difference on MMSE concentration component ( p ≤ .01), DS ( p ≤ .01), TMTB ( p ≤ .01), and COWAT ( p ≤ .01) scores, with the IDH1 wild group performing worse than the IDH1 mutant one. Age and tumor volume were inversely correlated with MMSE concentration component ( r = −4.78, p < .01), and with MMSE concentration ( r = −.401, p < .01), TMTB ( r = −.328, p < .01), and COWAT phonemic scores ( r = −.599, p < .01), respectively, but only for the IDH1 wild-type group. Analyses between age-matched subsamples of IDH1 groups revealed no age effect on NCF. Tumor grade showed nonsignificance on NCF ( p > .05) between the 2 IDH1 mutation subgroups of grade IV tumor patients. On the contrary, grade III group showed a significant difference in TMTB ( p < .01) and DS backwards ( p < .01) between IDH1 subgroups, with the mutant one outperforming the IDH1 wild one. Conclusions: Our findings indicate that IDH1 wild-type HGG patients present greater NCF impairment, in executive functions particularly, compared to IDH1 mutant ones, suggesting that tumor growth kinetics may play a more profound role than other tumor and demographic parameters in clinical NCF of HGG patients.